Genetic and clinical aspects of the transthyretin familial amyloid polyneuropathy: Report of a family - Kalcev, Goce; Barbov, Ivan (My University, 2019)
Abstract Introduction: Genetic testing in addition to clinical features marks this rare disease. Proving a mutation in the TTR gene is the most important tool in establishing a diagnosis. Materials and Methods: We report a Macedonian family from v. Bansko, Strumica (three brothers) Republic of North Macedonia, affected by transthyretin familial amyloid polyneuropathy. Results: Three brothers with TTR-FAP from North Macedonia were hospitalized at the Clinic of Neurology in Skopje. In addition, there was a positive finding from the genetic analysis. It showed present pathogen mutation in the TTP gene, Glu109Gln. The method used in this genetic testing consists of DNA Extraction with Phenol Chloroform, PCR Amplification of exon 3 of TTR gene, Direct DNA Sequencing with BigDye Terminator Sequencing Kit of exons of TTR gene by the method of Sanger and Analysis of ABI PRISM 3500 automatic genetic analyzer. The family gave information that there were deceased members of the same disease in the family. Congo red staining of samples from subcutaneous fat tissue aspiration biopsy was positive which is in favor of amyloid deposits Also, echocardiography registered left ventricular hypertrophy and dilatation at the same time. Electromyography with the neurography provided data for a generalized, symmetrical, chronic, partial sensor-motor neurogenic lesion with features predominantly of axonal neuropathy with signs of segmental demyelination. Conclusion: The clinical and genetic features of patients with TTR gene mutations are related to each other. Proving a mutation in the TTR gene clarifies the diagnostic puzzle and gives us the opportunity to begin therapy as soon as possible.
Keywords: FAP; Amyloid; TTR gene; mutation